The problems of modern youth and their reflection in literature (the story of Pak Min Gyu «The Mysterious Window» and Cho John Ra «The Fates of Man») - Тен, Ю. П. (Journal of Oriental Studies, 2018)
The article examines the search for the meaning of life of the young generation in the conditions of chronic anomie (lack of norm), which manifested itself in public life, which acquires special acuity in the era of globalization. Typical features of anomie are distinguished: disintegration of traditional value systems; Blurring the border between what is permitted and forbidden; Lack of a culture of freedom, inability to take responsibility for one’s own actions, aspiration for mimicry; The growth of selfishness, the fading of feelings of community, social responsibility, solidarity. The danger of a non-standard spiritual search for young people is that it can lead to spiritual and physical destruction of a person. Along with this process of agony of individualism, the iron hands of capital are being pushed to social death. Spiritually impoverished, lost in the darkness of contradictions, always ridiculous and pitiful in its attempts to find a cozy corner and hide in it, the person rapidly continues to fracture and becomes increasingly insignificant mentally. Feeling this, grasped by despair, conscious of it or concealing from itself, it rushes from corner to corner, seeking salvation. The hero «I» of the story Pak Min Gyu «The Mysterious Window», terrified of the inevitable future, sees salvation in his doom. Another character sees salvation in deliverance from his own child. This child becomes the meaning of life for the hero «I». «I» understands that he has no moral right to leave the baby on the cement floor of the roof.The meaning of life for a lonely, stranger among his own, Yun Hek (the hero of the story Cho John Re, «Fates of men»), a life that is not worth a penny, there are also children who are as alone as he is. Now they have a grandfather who will take care of themselves About them, and they will take care of it.